Skin aging handbook : an integrated approach to biochemistry and product development - Dayan, Nava (William Andrew, 2008)
Produce new breakthroughs in anti-aging products.
Keywords: Skin -- Aging.; Cosmetics.; Dermatologic agents.; Cosmetics industry.; Dermatologic agents industry.; Pharmaceutical chemistry.; elektronické knihy; electronic books